Public health in action: effective school health needs renewed international attention - Habib Benzian; Bella Monse; Vicente Belizario; Alexander Schratz; Murat Sahin; Wim van Palenstein Helderman (Taylor & Francis Group, 2012)
School health programmes as a platform to deliver high-impact health interventions are currently underrated by decision makers and do not get adequate attention from the international public health community. We describe the award-winning Fit for School Approach from the Philippines as an example of a large-scale, integrated, cost-effective and evidence-based programme that bridges the gap between sectors, and between evidence and practice. In view of the challenges to achieve the health and education related Millennium Development Goals (MDGs) in many countries, intensified efforts are required. We present the Fit for School Action Framework as a realistic and tested approach that helps to make schools places of public health for children and wider communities.